LINGUOGEOGRAPHICAL CARTOGRAPHY OF THE LEXICAL LAYER OF QARLUQ-TYPE UZBEK DIALECTS - Yoqubov Sodiqjon Latif o‘g‘li (International Journal of Literature and Language Studies, 2026)
This article analyzes the linguogeographic features of the vocabulary of Karluk-type Uzbek dialects. The study examines the territorial distribution, areal characteristics, and interrelations of lexical units specific to Karluk dialects based on linguogeographic maps. Using dialectological materials, the scope of usage, variants, and distribution boundaries of particular lexical items are identified, and the historical, ethnic, and social factors influencing their formation are explained. The article also reveals the relationship between the vocabulary of Karluk-type Uzbek dialects and the standard Uzbek language, as well as its areal connections with other dialects and subdialects. The findings of the research are of significant scholarly importance for Uzbek dialectology, linguoareal studies, and the geography of Turkic languages.